2011
DOI: 10.1089/scd.2010.0222
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stromal Cell Autologous Transplantation Ameliorates Pulmonary Arterial Hypertension Induced by Shunt Flow in Rat Models

Abstract: Hyperkinetic pulmonary arterial hypertension (PAH) severely influences the success of operation for congenital heart disease and deteriorates the prognosis of disease. Adipose-derived stromal cell (ADSC) is a good alternative multipotent stem cell for regeneration medicine. PAH rat models were established by arteriovenous shunt and ADSCs were isolated, cultured, and labeled in vitro. Twelve weeks after shunt operation, rats received an injection of 5 × 10(7) ADSCs. Two weeks after transplantation, hemodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…ADSCs were cultured from male Sprague–Dawley (SD) rats as previously described (Liu et al ., ). Briefly, inguinal adipose tissues isolated from rats were minced into small fragments and then were incubated with 0.075% collagenase type I (Sigma‐Aldrich, St. Louis, MO, USA) for 90 min at 37 °C with vigorous shaking for 20 sec at 15‐min interval.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…ADSCs were cultured from male Sprague–Dawley (SD) rats as previously described (Liu et al ., ). Briefly, inguinal adipose tissues isolated from rats were minced into small fragments and then were incubated with 0.075% collagenase type I (Sigma‐Aldrich, St. Louis, MO, USA) for 90 min at 37 °C with vigorous shaking for 20 sec at 15‐min interval.…”
Section: Methodsmentioning
confidence: 97%
“…Approximately 1 × 10 5 cells were incubated with antibodies against rat CD29, CD90, CD31, CD34, CD45, and CD106 (BD Biosciences, San Diego, CA, USA) for 30 min at 4 °C in the dark. To confirm the multipotency of ADSCs, the induction of adipocytes and osteoblasts was performed with adipogenic medium (DMEM containing 10% FBS, 0.5 mmol/L isobutylmethylxanthine, 200 μmol/L indomethacin, 10 μmol/L bovine insulin, and 1 μmol/L dexamethasone) and osteogenic medium (DMEM containing 10% FBS, 10 mmol/L β‐glycerophosphate, 0.1 μmol/L dexamethasone, and 50 μmol/L ascorbic acid), respectively (all the reagents were purchased from Sigma) (Liu et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…In addition, multiple studies of ischemia describe increased vascularization following ASC administration [145,150,[297][298][299][300][301][302][303]. Hemodynamic abnormalities in pulmonary arterial hypertension may be reversed using ASCs-a finding thought to be attributable to their induction of angiogenesis and increased formation of small, ISRN Stem Cells pulmonary arteries [304]. Increased capillary densities and higher blood flow have been reported in several studies using ASCs for the healing of skin wounds and improvement of skin flap survival [305,306].…”
Section: Asc-directed Tissue Regeneration: the Role Of Vascularizationmentioning
confidence: 99%
“…One frequently investigated cell population is constituted of BM-derived MSCs [23]. Several groups have shown that transplantation of BM-derived MSCs can reduce vascular remodeling and PAH in the monocrotaline (MCT) model [5456], in a high flow-induced model of PAH [57, 58] and a model of bronchopulmonary dysplasia and associated PH [59]. It is interesting that even intratracheal administration of MSCs results in reduced PAH in the MCT model [60].…”
Section: Vascular Regeneration and Repair For Pulmonary Hypertensionmentioning
confidence: 99%